Bottoms up: Coupling versus decoupling within Kı̄lauea’s magma supply system - Gaetano Ferrante; Helge M. Gonnermann (Journal of Volcanology and Geothermal Research, 2026)

P18-20 Building Bridges in Tobacco Harm Reduction: A Global Interlaboratory Initiative for Standardized Smoke and Aerosol Exposure Assessment - M. Caruso; R. Emma; P. Zuccarello; S. Rust; G. Carota; K. Poulas; F. Zadjali; A. Sun; V. Volarevic; R. Lesmana; M. Tobi; K. Mesiakaris; et al. (Toxicology Letters, 2025)

Evaluation of Trends in Influenza A and B Viruses in Wastewater and Human Surveillance Data: Insights from the 2022–2023 Season in Italy - P. Mancini; D. Brandtner; C. Veneri; G. Bonanno Ferraro; M. Iaconelli; S. Puzelli; M. Facchini; G. Di Mario; P. Stefanelli; L. Lucentini; A. Muratore; Paolo Torlontano; et al. (Food and Environmental Virology, 2025)

BeyondⓇ extender in donkey semen: evaluation at 5 °C and 17 °C over 7 days - M. Caldevilla; D. Neild; A. Ferrante; I. Cáceres Monie; C. Arraztoa; J. Plaza; J. Otero; M. Gambarotta; M. Miragaya (Journal of Equine Veterinary Science, 2025)

Tracking the Spread of the BA.2.86 Lineage in Italy Through Wastewater Analysis - C. Veneri; D. Brandtner; P. Mancini; G. Bonanno Ferraro; M. Iaconelli; E. Suffredini; M. Petrillo; G. Leoni; V. Paracchini; B. M. Gawlik; A. Marchini; Paolo Torlontano; et al. (Food and Environmental Virology, 2024)
The emergence of new SARS-CoV-2 variants poses challenges to global surveillance efforts, necessitating swift actions in their detection, evaluation, and management. Among the most recent variants, Omicron BA.2.86 and its sub-lineages have gained attention due to their potential immune evasion properties. This study describes the development of a digital PCR assay for the rapid detection of BA.2.86 and its descendant lineages, in wastewater samples. By using this assay, we analyzed wastewater samples collected in Italy from September 2023 to January 2024. Our analysis revealed the presence of BA.2.86 lineages already in October 2023 with a minimal detection rate of 2% which then rapidly increased, becoming dominant by January 2024, accounting for a prevalence of 62%. The findings emphasize the significance of wastewater-based surveillance in tracking emerging variants and underscore the efficacy of targeted digital PCR assays for environmental monitoring.

Radiocontamination level of mussels (M. Galloprovincialis) collected in italy from apulian coasts and assessed dose to population - G. Trotta; N. Bortone; V. Nardelli; O. Miedico; R. Damiano; M.A. Ferrante; M. Langianese; M. Nicolini; M. Iammarino (Regional Studies in Marine Science, 2024)

Indoor quality-oriented approach for the performance evaluation of building retrofit with façade transformation: Case study of student dormitory in Mediterranean climate - A. Gigante; D. Papadaki; C. Mazzoli; V. Ntouros; R.F. De Masi; M.-N. Assimakopoulos; Annarita Ferrante (Energy and Buildings, 2024)

Preharvest melatonin application mitigates arsenic-induced oxidative stress and improves vase life of tuberose (Polianthes tuberosa L.) cut flowers - Faisal Zulfiqar; Anam Moosa; Hayssam M. Ali; Antonio Ferrante; Muhammad Mudassir Nazir; Abdullah Makhzoum; Tarek M.A. Soliman (South African Journal of Botany, 2023)

Evaluation of equine semen frozen in extenders free of animal proteins - Mariana L Caldevilla; Alejandro A Ferrante; Camila Tossici; Julieta C Otero; Mariana C Gambarotta; Claudia C Arraztoa; Marcelo H Miragaya; Deborah M Neild (Journal of Equine Veterinary Science, 2023)

Comparison of different cryoprotectants for freezing donkey jack (Equus asinus) semen - Santiago L Bruno; Deborah M Neild; Jessica P Plaza; Alejandro A Ferrante; María I Carretero; Gustavo EA Olivieri; Carolina P Bianchi; Marcelo H Miragaya (Journal of Equine Veterinary Science, 2023)

Wastewater surveillance of SARS-CoV-2 variants in October–November 2022 in Italy: detection of XBB.1, BA.2.75 and rapid spread of the BQ.1 lineage - G. La Rosa; D. Brandtner; G. Bonanno Ferraro; C. Veneri; P. Mancini; M. Iaconelli; L. Lucentini; C. Del Giudice; L. Orlandi; Achille Palma; Adelaide Calabria; Agnese Carnevali; et al. (Science of The Total Environment, 2023)

Modeling hypoxia-related inflammation scenarios - P. Ferrante; L. Preziosi; M. Scianna (Mathematical Biosciences, 2023)

User-Centered Development and Patient Acceptability Testing of a Health-Coaching Intervention to Enhance Cancer Survivorship Follow-up in Primary Care - Denalee M. O’Malley; Stacy N. Davis; Rahwana Amare; Bianca Sanabria; Brittany Sullivan; Katie A. Devine; Jeanne M. Ferrante; Patricia A. Findley; Suzanne M. Miller; Shawna V. Hudson (Journal of Cancer Education, 2022)

A novel morphological phenotype does not ensure reduced biotic resistance on an oceanic island - M. Ferrante; R. Nunes; L. Lamelas-López; G. L. Lövei; P. A. V. Borges (Biological Invasions, 2022)

Genome-wide SNP analysis of three moose subspecies at the southern range limit in the contiguous United States - Jason A. Ferrante; Chase H. Smith; Laura M. Thompson; Margaret E. Hunter (Conservation Genetics, 2022)
Genome-wide evaluations of genetic diversity and population structure are important for informing management and conservation of trailing-edge populations. North American moose ( Alces alces ) are declining along portions of the southern edge of their range due to disease, species interactions, and marginal habitat, all of which may be exacerbated by climate change. We employed a genotyping by sequencing (GBS) approach in an effort to collect baseline information on the genetic variation of moose inhabiting the species’ southern range periphery in the contiguous United States. We identified 1920 single nucleotide polymorphisms (SNPs) from 155 moose representing three subspecies from five states: A. a. americana (New Hampshire), A. a. andersoni (Minnesota), and A. a. shirasi (Idaho, Montana, and Wyoming). Molecular analyses supported three geographically isolated clusters, congruent with currently recognized subspecies. Additionally, while moderately low genetic diversity was observed, there was little evidence of inbreeding. Results also indicated > 20% shared ancestry proportions between A. a. shirasi samples from northern Montana and A. a. andersoni samples from Minnesota, indicating a putative hybrid zone warranting further investigation. GBS has proven to be a simple and effective method for genome-wide SNP discovery in moose and provides robust data for informing herd management and conservation priorities. With increasing disease, predation, and climate related pressure on range edge moose populations in the United States, the use of SNP data to identify gene flow between subspecies may prove a powerful tool for moose management and recovery, particularly if hybrid moose are more able to adapt.

Correction to: Sant’Imbenia (Alghero): further archaeometric evidence for an Iron Age market square - M. Clemenza; B. Billeci; M. Carpinelli; M. Ferrante; E. Fiorini; G. Gasperetti; S. Nisi; P. Oliva; V. Sipala; P. R. Trincherini; I. M. Villa; M. Rendeli (Archaeological and Anthropological Sciences, 2021)

Sant’Imbenia (Alghero): further archaeometric evidence for an Iron Age market square - M. Clemenza; B. Billeci; M. Carpinelli; M. Ferrante; E. Fiorini; G. Gasperetti; S. Nisi; P. Oliva; V. Sipala; P. R. Trincherini; I. M. Villa; M. Rendeli (Archaeological and Anthropological Sciences, 2021)
Lead isotope compositions were determined for 18 metal objects from the archaeological site of Sant’Imbenia, NW Sardinia, dating to the end of the ninth century BCE onwards. The provenance of some objects is unambiguously traced to SW Sardinia; other objects could derive either from central Sardinia or the Iberian coastal ranges. The variety of the provenances attests to a wide trade network that spanned the entire island of Sardinia and extended to the Iberian sites.

Search for top‐down and bottom‐up drivers of latitudinal trends in insect herbivory in oak trees in Europe - Elena Valdés‐Correcher; Xoaquín Moreira; Laurent Augusto; Luc Barbaro; Christophe Bouget; Olivier Bouriaud; Manuela Branco; Giada Centenaro; György Csóka; Thomas Damestoy; Jovan Dobrosavljević; Mihai‐Leonard Duduman; et al. (Global Ecology and Biogeography, 2021)
Aim The strength of species interactions is traditionally expected to increase toward the Equator. However, recent studies have reported opposite or inconsistent latitudinal trends in the bottom‐up (plant quality) and top‐down (natural enemies) forces driving herbivory. In addition, these forces have rarely been studied together thus limiting previous attempts to understand the effect of large‐scale climatic gradients on herbivory. Location Europe. Time period 2018–2019. Major taxa studied Quercus robur . Methods We simultaneously tested for latitudinal variation in plant–herbivore–natural enemy interactions. We further investigated the underlying climatic factors associated with variation in herbivory, leaf chemistry and attack rates in Quercus robur across its complete latitudinal range in Europe. We quantified insect leaf damage and the incidence of specialist herbivores as well as leaf chemistry and bird attack rates on dummy caterpillars on 261 oak trees. Results Climatic factors rather than latitude per se were the best predictors of the large‐scale (geographical) variation in the incidence of gall‐inducers and leaf‐miners as well as in leaf nutritional content. However, leaf damage, plant chemical defences (leaf phenolics) and bird attack rates were not influenced by climatic factors or latitude. The incidence of leaf‐miners increased with increasing concentrations of hydrolysable tannins, whereas the incidence of gall‐inducers increased with increasing leaf soluble sugar concentration and decreased with increasing leaf C : N ratios and lignins. However, leaf traits and bird attack rates did not vary with leaf damage. Main conclusions These findings help to refine our understanding of the bottom‐up and top‐down mechanisms driving geographical variation in plant–herbivore interactions, and indicate the need for further examination of the drivers of herbivory on trees.

Genome editing in diatoms: achievements and goals - Peter G. Kroth; Atle M. Bones; Fayza Daboussi; Maria I. Ferrante; Marianne Jaubert; Misha Kolot; Marianne Nymark; Carolina Río Bártulos; Andrés Ritter; Monia T. Russo; Manuel Serif; Per Winge; et al. (Plant Cell Reports, 2018)

Characterisation of Pseudomonas syringae isolates from apricot orchards in north-eastern Italy - D. Giovanardi; P. Ferrante; M. Scortichini; E. Stefani (European Journal of Plant Pathology, 2018)

Treatment and outcome of subdural hematoma in patients with spontaneous intracranial hypotension: a report of 35 cases - Enrico Ferrante; Fabio Rubino; Federica Beretta; Caroline Regna-Gladin; M. Mirko Ferrante (Acta Neurologica Belgica, 2018)

Ground-level predation on artificial caterpillars indicates no enemy-free time for lepidopteran larvae - M. Ferrante; G. Barone; M. Kiss; E. Bozóné-Borbáth; G. L. Lövei (Community Ecology, 2017)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Emended description of Pseudomonas syringae pv. avellanae, causal agent of European hazelnut (Corylus avellana L.) bacterial canker and decline - M. Scortichini; P. Ferrante; L. Cozzolino; A. Zoina (European Journal of Plant Pathology, 2016)

Pseudomonas syringae pv. actinidiae strains isolated from past and current epidemics to Actinidia spp. reveal a diverse population structure of the pathogen - P. Ferrante; Y. Takikawa; M. Scortichini (European Journal of Plant Pathology, 2015)

Insecticidal and anti-microbial activity of bio-oil derived from fast pyrolysis of lignin, cellulose, and hemicellulose - Mohammad M. Hossain; Ian M. Scott; Brian D. McGarvey; Kenneth Conn; Lorenzo Ferrante; Franco Berruti; Cedric Briens (Journal of Pest Science, 2015)

Effects of Pseudomonas fluorescens Seed Bioinoculation on Heavy Metal Accumulation for Mirabilis jalapa Phytoextraction in Smelter-Contaminated Soil - M. Petriccione; D. Di Patre; P. Ferrante; S. Papa; G. Bartoli; A. Fioretto; M. Scortichini (Water, Air, & Soil Pollution, 2013)

The interactions of age, sex, body mass index, genetics, and steroid weight-based doses on tacrolimus dosing requirement after adult kidney transplantation - P. Stratta; M. Quaglia; T. Cena; R. Antoniotti; R. Fenoglio; A. Menegotto; D. Ferrante; A. Genazzani; S. Terrazzino; C. Magnani (European Journal of Clinical Pharmacology, 2012)

Cadmium Accumulation and Antioxidant Responses in Sparus aurata Exposed to Waterborne Cadmium - T. Cirillo; R. Amodio Cocchieri; E. Fasano; A. Lucisano; S. Tafuri; M. C. Ferrante; E. Carpenè; G. Andreani; G. Isani (Archives of Environmental Contamination and Toxicology, 2012)

Regional surveillance of emergency-department visits for outpatient adverse drug events - A. Capuano; A. Irpino; M. Gallo; L. Ferrante; M. L. Illiano; B. Rinaldi; A. Filippelli; F. Rossi (European Journal of Clinical Pharmacology, 2009)

Demographic and spatial analysis of a population of Juniperus oxycedrus L. in an abandoned grassland - M Baldoni; E Biondi; L Ferrante (Plant Biosystems, 2004)

Dendritic I h Selectively Blocks Temporal Summation of Unsynchronized Distal Inputs in CA1 Pyramidal Neurons - M. Migliore; L. Messineo; M. Ferrante (Journal of Computational Neuroscience, 2004)

JC virus small tumor antigen promotes S phase entry - M Safak; R Biffi; S Woolridge; I Kudret; IK Sariyer; I Akan; P Ferrante; K Khalili; M Safak (Journal of NeuroVirology, 2004)

Agnoprotein and its coding sequences play regulatory roles in JC virus gene transcription and replication in glial cells - M Safak; R Biffi; S Radhakrishnan; S Woolridge; I K Sariyer; I Akan; J Gordon; S Amini; P Ferrante; K Khalili (Journal of NeuroVirology, 2004)

Persistent Organochlorine Pollutants in Liver of Birds of Different Trophic Levels from Coastal Areas of Campania, Italy - B. Naso; D. Perrone; M. C. Ferrante; A. Zaccaroni; A. Lucisano (Archives of Environmental Contamination and Toxicology, 2003)

ISSR-PCR technique: a useful method for characterizing new allotetraploid somatic hybrids of mandarin - M.-T. Scarano; L. Abbate; S. Ferrante; S. Lucretti; N. Tusa (Plant Cell Reports, 2002)

Subgrouping of human rotavirus strains by complement fixation, indirect double-antibody sandwich enzyme-linked immunosorbent assay and solid-phase immune electron microscopy - G. Gerna; M. Torsellini; N. Passarani; M. Battaglia; E. Percivalle; A. Sarasini; D. Torre; P. Ferrante (Archives of Virology, 1984)